Insurers' Investment in Infrastructure Projects: Overview and Treatment under Solvency II - Gatzert, Nadine; Kosub, Thomas (Geneva Papers on Risk and Insurance-Issues and Practice, 2014)
The financial market environment poses serious challenges for insurance companies to provide stable returns on a long-term basis, as particular traditional asset classes are currently characterised by generally low interest rates and high volatility. Against this background, the aim of this paper is to study infrastructure investments from an insurer’s perspective. In particular, based on a categorisation of different types of infrastructure investments, we provide an overview of main characteristics along with risks and chances. In addition, the treatment of different infrastructure investments under Solvency II regulations is studied, which can have a considerable impact on an insurer’s asset management decisions. The study shows that the attractiveness of infrastructure investments strongly depends on the type of investment and its treatment under Solvency II and that considerable risks can be involved.
WiSo-Import:2015-03-26:5069